2008
DOI: 10.1002/jnr.21926
|View full text |Cite
|
Sign up to set email alerts
|

Protective function of taurine in glutamate‐induced apoptosis in cultured neurons

Abstract: Previously, we showed that taurine protects neurons against glutamate-induced excitotoxicity by inhibiting the glutamate-induced increase of [Ca2+](i). In this study, we report that taurine prevents glutamate-induced chromosomal condensation, indicating that taurine inhibits glutamate-induced apoptosis. We found that Bcl-2 was down-regulated while Bax was up-regulated by glutamate treatment, and these changes were prevented in the presence of taurine. We have also shown that taurine inhibits glutamate-induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(77 citation statements)
references
References 47 publications
1
70
0
2
Order By: Relevance
“…One is associated with an exaggerated and prolonged rise in intracellular Ca 2+ concentration following the over-stimulation of NMDA receptors [21,22] . Another involves the oxidative injury pathway which is independent of NMDA receptors [11] and can be specifically inhibited by vitamin E, the caspase inhibitor, extracellular cystine in an elevated level, and the removal of extracellular glutamate [23,24] .…”
Section: Discussionmentioning
confidence: 99%
“…One is associated with an exaggerated and prolonged rise in intracellular Ca 2+ concentration following the over-stimulation of NMDA receptors [21,22] . Another involves the oxidative injury pathway which is independent of NMDA receptors [11] and can be specifically inhibited by vitamin E, the caspase inhibitor, extracellular cystine in an elevated level, and the removal of extracellular glutamate [23,24] .…”
Section: Discussionmentioning
confidence: 99%
“…In the ischemic hypothalamic nucleus of mice, taurine also attenuated the expression of caspase-8 and caspase-9 (Taranukhin et al 2008 ;Leon et al 2009 ) .…”
Section: Discussionmentioning
confidence: 88%
“…[53] [55] In addition, we have also demonstrated that glutamate-induced activation of calpain is inhibited by taurine resulting in decrease of formation of hetero-dimers of Bcl-2 and Bax and the subsequent release of cytochrome C and the apoptosis cascade. [56] The effect of taurine on brain astrocytes might be involved in the mechanism by which this amino acid prevents brain edema in in vivo conditions. Cauli et al (2014) [57] mentioned that the predominant role of neuroinflammation rather than brain edema in the pathogenesis of CNS injury in HE.…”
Section: World Journal Of Pharmacy and Pharmaceutical Sciencesmentioning
confidence: 99%